MAKNA KRITIK SOSIAL DALAM PUISI (Studi Analisis Wacana Kritis pada Puisi “Dongeng Marsinah” Karya Sapardi Djoko Damono) - Alfiansyah Alfiansyah; Hamidah Hamidah; Indrawati Indrawati (Tabayyun: Journal of Journalism, 2020)
ABSTRACT This research was started from the authors’ interest in social criticisms related to the case of human rights violations experienced by the watch factory worker from PT. Catur Putra Surya (CPS) named Marsinah during the New Order period. Poetry itself is one of the communication media that can be used by someone to give social criticism against an occasion. In a poem "Dongeng Marsinah", there were many metaphors that represented the reality of Marsinah murder case. While, in order to learn the meaning of social critics was contained in the poem “Dongeng Marsinah”, researchers conductednthe research used a critical approach, model Teun A. Van Dijk that had three dimensions of analysis. That were text dimensions, social cognition, and social context dimensions, so that researchers could find a representation of the meaning of social criticism of Marsinah’s violations of human rights. Through observations, documentation, and interviews were conducted by researchers, finally found social criticisms of marsinah case contained in the poem. The results showed that Sapardi Djoko Damono wanted to show social criticism and how the reality that Marsinah experienced during her time as a watch factory worker, where she had to fight desperately for the severe rights of workers, until finally she had to be killed in a terrible accident. To become a reader of a poem, we must be prepared to be confronted with the thoughts made by the author of the text of the poem as a description of the reality that cools along with his ideology through the implied messages in the text. Keywords: Critical Discourse Analysis, Poetry, Marsinah.